Strategies for thromboprophylaxis in Fontan circulation: a network meta-analysis. (3rd October 2022) - Van Den Eynde, J; Possner, M; Alahdab, F; Veldtman, G; Goldstein, B; Rathod, R; Hoskoppal, A; Saraf, A; Feingold, B; Alsaied, T
Abstract: Introduction: The Fontan circulation is associated with an increased risk of thromboembolic events. However, the optimal strategy for thromboprophylaxis in this population remains unknown. Purpose: The aim of this study was to compare the efficacy and safety of aspirin, warfarin, and non-vitamin K antagonist oral anticoagulants (NOACs) in a network meta-analysis using no thromboprophylaxis as a common comparator. Methods: A comprehensive search was performed in Medline, Embase, Cochrane, and Scopus to identify relevant observational studies and randomized controlled trials published by February 14th, 2022. The primary efficacy outcome was thromboembolic events at the longest available follow-up, while major bleeding was a secondary safety outcome. Frequentist network meta-analyses were conducted to estimate the incidence rate ratios (IRRs) with corresponding 95% confidence intervals (CI) of both outcomes. Finally, ranking of treatments was performed based on probability (P) score. Results: A total of 25 studies were included, encompassing 26, 823 patient-years (aspirin: 11, 948; warfarin: 11, 354; NOAC: 346; no thromboprophylaxis: 3, 175). When compared to no thromboprophylaxis, NOACs (IRR 0.12, 95% CI 0.03–0.41), warfarin (IRR 0.23, 95% CI 0.14–0.36), and aspirin (IRR 0.26, 95% CI 0.16–0.40) were all associated with significantly lower rates of thromboembolic events. However, the network meta-analysis revealed no significant differences in the rates of major bleeding for any of the strategies, although bleeding risk was numerically higher with NOACs and warfarin (NOAC: IRR 1.45, 95% CI 0.28–7.43; warfarin: IRR 1.38, 95% CI 0.41–4.69; and aspirin: IRR 0.72, 95% CI 0.20–2.58, Figure 1). Rankings, which simultaneously analyze competing interventions, suggested NOACs as the best strategy to prevent thromboembolic events (P score 0.919), followed by warfarin (P score 0.615), aspirin (P score 0.466), and no thromboprophylaxis (P score 0.001). Conclusions: NOACs were associated with the greatest reduction in thromboembolic events with no significant difference in major bleeding when compared with warfarin and aspirin. Funding Acknowledgement: Type of funding sources: None.